PENGEMBANGAN APLIKASI INSTRUMEN GAMELAN GONG KEBYAR BERBASIS ANDROID - Surya Pratama Wardhana, I Putu; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2014)
Gong Kebyar is one of barunganBali’s